Integrating the management of ultra-processed food addiction into type 2 diabetes care: a clinical response to De Silva et al, (2025) and practical recommendations for practitioners - Bennett, Ellen; Myers-Morrison, Cynthia; Unwin, David (Frontiers in Psychiatry, 2026)
Ultra-processed food addiction (UPFA) is increasingly recognised as a clinically meaningful construct with implications for metabolic and psychiatric health. Recent evidence suggests that approximately 30% of individuals living with type 2 diabetes (T2D) may also experience UPFA, a co-occurrence associated with poorer glycaemic control and increased morbidity. Despite this, UPFA is rarely addressed in routine diabetes care. This article provides a clinical response to da Silva et al. (2025) and outlines practical recommendations for healthcare professionals supporting individuals with overlapping T2D and UPFA. Drawing on current literature and clinical experience, we propose a structured approach incorporating screening, dietary strategies, behavioural support, and medication management. Screening can be facilitated using brief, accessible tools such as CRAVED, enabling early identification of addictive eating patterns. Addiction-informed nutritional support — including structured exclusion of trigger foods — may improve dietary adherence and glycaemic outcomes, particularly when supported by continuous glucose monitoring and behavioural relapse-prevention strategies. Pharmacological interventions such as GLP-1 receptor agonists may also play a role in reducing appetite and food cravings. We further highlight the value of professionally facilitated and peer-led support groups (e.g., Liberate, SUGARx Global, 12-step models) and the need for integrated multidisciplinary care. UPFA represents both a clinical barrier and a therapeutic opportunity: recognising and addressing it may enhance metabolic and psychological outcomes. Future research should evaluate UPFA-informed interventions in randomised trials to guide clinical practice.